PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Riyandi, Rahmat (Universitas Riau Kepulauan, 2015)
The purpose of this study is to investigate and analyze the influence of leadership style on the performance and motivation of employees of PT. Bank Danamon Indonesia, Tbk Branch Batam. The population used in this study were all employees at PT. Bank Danamon Indonesia, Tbk Branch Batam by 120 people. 55 While the sample is obtained from the calculation using the formula Slovin. This research was conducted using multiple linear regression with quantitative analysis, t-test (partial), F test (simultaneous) and coefficient of determination (R2). Based on the results of this study concluded: there is positive and significant correlation between leadership styles on employee performance, there is no significant effect between work motivation on employee performance and significant relationship between leadership style and work motivation on employee performance. Variable leadership style became dominant variables that influence employee performance analysis is based on the calculation of the standard beta coefficient has the greates value. The conclusion of this study is the style of leadership as important variables that affect the performance of employees. Therefore, it is advisable to pay more attention to the leadership of these two variables to produce a good performance of employees at PT. Bank Danamon Indonesia, Tbk Branch Batam.